Learning Objective Mapping of the National Competence-Based Learning Objectives Catalogue of Medicine in Orthopaedic Surgery – an Option to Implement an Existing Structure - Schöbel, Tobias; Heyde, Christoph-Eckhard; Postler, Anne Elisabeth; Pieroh, Philipp (Zeitschrift für Orthopädie und Unfallchirurgie, 2025)
With the new licensing regulations and the National Competence-Based Learning Objectives Catalogue for Medicine (NKLM), the learning objectives and certificates of achievement are no longer assigned to specific subjects. In addition to the opportunity for the subject of orthopaedics and trauma surgery to present itself more prominently and at an earlier stage, there is also a need to identify the relevant subject-related learning objectives in order to integrate them into the curricula and prepare for internal faculty discussions on teaching assignments. At present, it remains unclear whether the new licensing regulations will be accompanied by the initially planned complete restructuring in the form of the so-called Z-curriculum, but the new learning objectives of the NKLM will become part of the training for future doctors.The learning objectives contained in the current draft of the NKLM from December 2023 were screened and evaluated by two teaching coordinators using the dual control principle. The learning objectives that should and can be meaningfully taught by the O & U were selected from the 2646 formulated contents. A total of 276 (10.32%) learning objectives were detected for the teaching of O & U and 2399 (89.68%) were excluded. The selected learning objectives were then assigned to the existing courses and the institute’s own teaching was optimised accordingly in preparation.In this study, the learning objectives of the NKLM were compared with the current learning objectives of O & U at Leipzig University and the learning objectives of the NKLM were integrated into the curricula. Of the NKLM, 10.32% of the learning objectives relate to the subject O & U, which underlines its importance. In addition, the approach presented here shows that the learning objectives of the NKLM can be quickly implemented in an existing curriculum.Mit der neuen Approbationsordnung und dem Nationalen Kompetenzbasierten Lernzielkatalog Medizin (NKLM) werden die Lernziele und Leistungsnachweise nicht mehr fächerbezogen zugeordnet. Auch für das Fach Orthopädie und Unfallchirurgie (O & U) besteht die Notwendigkeit der Identifikation der fachbezogenen relevanten Lernziele, um diese in die Lehrpläne zu integrieren und sich auf fakultätsinterne Diskurse über Lehrdeputate vorzubereiten. Aktuell bleibt unklar, ob und wann mit der neuen Approbationsordnung auch die initial geplante komplette Umstrukturierung in Form des sog. Z-Curriculums kommt, unabhängig davon werden die neuen Lernziele des NKLM zum Bestandteil der Ausbildung für zukünftige Mediziner*innen.Im 1. Schritt wurden die im aktuellen Entwurf des NKLM vom Dezember 2023 enthaltenen Konsultationsanlässe, Erkrankungen und Lernziele durch 2 Lehrkoordinatoren im Vieraugenprinzip gescreent und hinsichtlich der Relevanz für O & U bewertet. Im 2. Schritt wurde die aktuelle Lehrstruktur entsprechend dem geltenden Gegenstandkatalog analysiert und die Struktur bez. der Veranstaltungen (Vorlesung/Unterricht am Krankenbett/Seminar) hinterlegt. Im 3. Schritt erfolgte die Implementierung der für O & U relevanten Lernziele in die aktuell bestehende Lehrstruktur.Aus 2646 Einträgen des NKLM wurden 276 (10,32%) Lernziele für die Lehre der O & U detektiert. Aktuell wird ein wöchentlicher Kurs vor dem Ersten Staatsexamen und im klinischen Studienteil 43 Vorlesungen und 16 Seminarveranstaltungen durch die O & U gelehrt. In die bestehende Lehrstruktur konnten 85 Konsultationsanlässe/Erkrankungen und 129 Lernziele integriert werden, diese werden entsprechend der Dimension der Wissenstiefe redundant gelehrt.
Keywords: medical training; medical studies; licensing regulations